2019
DOI: 10.3390/biom9090406
|View full text |Cite
|
Sign up to set email alerts
|

Creatine for the Treatment of Depression

Abstract: Depressed mood, which can occur in the context of major depressive disorder, bipolar disorder, and other conditions, represents a serious threat to public health and wellness. Conventional treatments are not effective for a significant proportion of patients and interventions that are often beneficial for treatment-refractory depression are not widely available. There is, therefore, an immense need to identify novel antidepressant strategies, particularly strategies that target physiological pathways that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 191 publications
0
32
0
1
Order By: Relevance
“…Recently, CKB was also differentially expressed in a single-nucleus study of the prefrontal cortex in MDD 59 . Creatine kinase isoenzymes, including CKB, which is specific to the brain, converts creatine to phosphocreatine to efficiently meet energy demands 60 . In rodents, creatine kinase isoenzymes are sexually dimorphic with higher activity in males than females 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, CKB was also differentially expressed in a single-nucleus study of the prefrontal cortex in MDD 59 . Creatine kinase isoenzymes, including CKB, which is specific to the brain, converts creatine to phosphocreatine to efficiently meet energy demands 60 . In rodents, creatine kinase isoenzymes are sexually dimorphic with higher activity in males than females 61 .…”
Section: Discussionmentioning
confidence: 99%
“…There is mounting evidence for significant involvement of creatine in the pathophysiology of major depressive disorder (MDD) [70]. Several studies have shown that Akt and its downstream molecular targets effect MDD and may be targets for depression treatment [71][72][73].…”
Section: Antidepressant-like Effect Mediated By Fndc5/bdnf/akt In Micmentioning
confidence: 99%
“…results, creatine studies have also found sex-specific signals in the context of depression. Creatine kinase isoenzymes, including CKB, which is specific to the brain, converts creatine to phosphocreatine to efficiently meet energy demands 57 . In rodents, creatine kinase isoenzymes are sexually dimorphic with higher activity in males than females 58 .…”
Section: Mirroring Our Ckbmentioning
confidence: 99%